Understanding the World in the Early Years Foundation Stage: practitioners' perspectives of best practice and effective provision. Issue 8 (17th November 2022) - Forrester, Gillian; Pugh, Jim; Hudson, Ruth; Rowley, Jane
ABSTRACT: This article reports on a research project which investigated early years practitioners' perspectives of best practice and effective provision in relation to the Understanding the World area of learning of the Early Years Foundation Stage. This area of learning focuses on 'People and Communities', 'The World', and 'Technology'. A mixed-methods approach utilising an online survey and semi-structured interviews generated data from early years practitioners located in nurseries and primary schools in Stoke-on-Trent, England. Practitioners' views were ascertained along with the identification of perceived obstacles impeding children's learning, social and cognitive development, and attainment.